Da extrajudicialização de conflitos envolvendo a adminstração pública no âmbito das serventias extrajudiciais. - Maciel, Thiago Mota (2024)
The purpose of the Dissertation is to study the use by the Public Authorities of consensual methods as conflict resolution mechanisms. Considering the excessive litigation that exists in the Brazilian Judiciary in which the Public Administration figures as the biggest litigant, according to the Justice in Numbers report, it is proposed to use extrajudicial means of resolving demands, faster and with more capillarity than the Judiciary to resolve various conflicts; providing greater access to justice. To this end, an analysis of the system of extrajudicial dispute resolution and the policy to encourage the use of mechanisms is carried out, highlighting the New Code of Civil Procedure and Laws 13,140 of 2015, 14,133 of 2021 and the policies for extrajudicialization of present demands in the Provisions in the National Council of Justice, especially Provision No. 67. Aiming to insert Extrajudicial Services as instruments for resolving disputes involving the Public Administration in this context and demonstrating that there is no offense to the unavailability of the public interest, a literature and legislative review was carried out on consensual methods of conflict resolution, reading of consensuality in Public Administration, public interest and the concept of state available patrimonial rights. Among the alternative means, mediation and conciliation are deepened within the scope of extrajudicial services. And the legislative incentives to define consensual procedures for the mechanism and conclude that it can reduce the number of demands overwhelmed by the Judiciary, which are already many. The rules introduced by Laws 13,140/2015, 14,133/2021 and the relationship of conciliation and mediation in extrajudicial services in the State of Pernambuco through Joint Provision 02/2019, to conclude that they can contribute to the continuity of the execution of contracts, notably in those of technical and legal complexity involved, which have great social repercussions.